BIODIVERSITY AND ABUNDANCE OF PHYTOPLANKTON IN RICE-FISH FARMING SYSTEM - Mustika Palupi,; Kasprijo,; Rudi Wijaya,; Rizky Ade Chanda,; Rais Fikri Azhari,; Ren Fitriadi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Rice-fish farming system that is purposed to maximize land use by adding fish farming to its systems. In the Rice-fish farming system, the fish farm serves as a solution to overcome pests so it can provide benefits for the farmers. Fish farm maintenance is considered to be a solution to reduce farmers expenditures in the use of fertilizers. The reason is in the fish-maintaining process, fish will naturally excrete dirt which has a function as organic fertilizer which will increase the fertility of the waters. The purpose of this study was to determine the composition of phytoplankton as well as the physical and chemical quality of the water in several Rice-fish farming system stations in Panembangan Village so that the condition of the ecosystem can be detected whether it is in good or bad condition. The Results showed that the diversity index value ranged from 0.61-1.99. The uniformity index value was obtained in the range of 0.15 – 0.50 and the dominance index value was obtained in the range of 0.20 – 0.72. While, the four stations still have good water quality, the conditions in the Rice-fish farming system area of Panembangan Village are still suitable for the growth of organisms.